2018
DOI: 10.31768/2312-8852.2018.40(4):288-298
|View full text |Cite
|
Sign up to set email alerts
|

Ber Gene Polymorphisms Associated With Key Molecular Events in Bladder Cancer

Abstract: Aim: Base excision repair (BER) gene polymorphisms are known to play an independent role in predisposition to developing different cancers as well as to be associated with clinicopathological traits of the disease modifying its clinical outcomes. One of the underlying mechanisms is presumed to include interplay between BER gene polymorphisms and key mutational, epigenetic and chromosomal events in tumor tissues. The present study was aimed at elucidating potential gene-gene interaction and assessing their mutu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…Indeed, the frequency of the oncogenic phosphatidylinositol 3-kinase (PIK3CA) mutations was reduced in smokers of heterozygous genotype (Ser/Cys) and minor allele (Cys) carriers. On the contrary, the same polymorphism correlated with an increased frequency of mutations in the RAS loci and affected the levels of runt-related transcription factor 3 (RUNX3) and ISL LIM homeobox 1 (ISL1) methylation (277). In addition, it has been shown that OGG1 Ser326Cys homozygous genotype (Cys/Cys) represents a risk factor for childhood leukaemia ( 278).…”
Section: Ber Polymorphisms and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the frequency of the oncogenic phosphatidylinositol 3-kinase (PIK3CA) mutations was reduced in smokers of heterozygous genotype (Ser/Cys) and minor allele (Cys) carriers. On the contrary, the same polymorphism correlated with an increased frequency of mutations in the RAS loci and affected the levels of runt-related transcription factor 3 (RUNX3) and ISL LIM homeobox 1 (ISL1) methylation (277). In addition, it has been shown that OGG1 Ser326Cys homozygous genotype (Cys/Cys) represents a risk factor for childhood leukaemia ( 278).…”
Section: Ber Polymorphisms and Cancermentioning
confidence: 99%
“…BER polymorphism can affect the methylation status of some tumour suppressor genes, as previously mentioned. For instance, focusing on XRCC1, in a study which considered a cohort of patients with bladder cancer, the XRCC1 Arg399Gln (rs25487) heterozygous (Arg/Gln) genotype increased the frequency of p16 and TIMP3 methylation (277).…”
Section: Ber Polymorphisms and Cancermentioning
confidence: 99%
“…Similarly, Tayyaba et al showed that such a variant contributes to urothelial bladder carcinoma [44]. In parallel, rs1052133 OGG1 variant was linked to various cancers as breast, colon, stomach, kidney, orolaryngeal, bladder, colorectal cancers, and leukemia [45][46][47][48][49][50]. Rs113561019 OGG1 was suggested as a low penetrance contributor to colorectal cancer [51].…”
Section: Ber Variants/mutations and Cancer (Skin And Internal)mentioning
confidence: 99%
“…С полиморфизмом в гене OGG1 связывают риски развития многих заболеваний: рака легкого [2], поджелудочной железы [3], молочной железы [4], яичника [5], колоректального рака [6], рака желудка [7], мочевого пузыря [8], щитовидной железы [9], простаты [10], а также нейродегенеративных процессов в мозге, болезни Альцгеймера [11], острой [12] и хронической миелоидной лейкемии [13], диабета 2-го типа [14], рассеянного склероза [15], возрастной катаракты [16], прогрессирования первичной открытоугольной глаукомы [17], мужской инфертильности [18], повышенной смертности от кардиоваскулярных заболеваний [19], тяжести отравления пестицидами [20].…”
Section: оригинальные исследования медицинская генетика 2021 №9unclassified